2012
DOI: 10.1111/j.1651-2227.2012.02607.x
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance enterography guiding treatment in children with Crohn’s jejunoileitis

Abstract: Magnetic resonance enterography identifies disease involvement in the small bowel in young patients with Crohn's disease and may guide decisions on the need for intestinal surgery or adjustment of medication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…MRE has been found to have a sensitivity of 83 to 94 per cent and specificity of 90 to 100 per cent for detecting CD in several studies. [7][8][9] In a prospective study of 50 patients with symptomatic CD, there was no significant difference between the sensitivity and specificity of MRE compared with that of CT in detecting the presence of small bowel CD. 10 Furthermore, it was concluded that although both MRE and CT have high positive predictive values for detecting CD (93 and 91%, respectively), the negative predictive values (47 and 54%, respectively) are low.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…MRE has been found to have a sensitivity of 83 to 94 per cent and specificity of 90 to 100 per cent for detecting CD in several studies. [7][8][9] In a prospective study of 50 patients with symptomatic CD, there was no significant difference between the sensitivity and specificity of MRE compared with that of CT in detecting the presence of small bowel CD. 10 Furthermore, it was concluded that although both MRE and CT have high positive predictive values for detecting CD (93 and 91%, respectively), the negative predictive values (47 and 54%, respectively) are low.…”
Section: Discussionmentioning
confidence: 95%
“…7 Although it does not detect superficial lesions, MRE can detect stenoses, thickening, and hyperemia of the bowel wall, extramural complications, and abscesses. 8 Furthermore, magnetic resonance imaging (MRI) is excellent at differentiating active inflammation from fibrosis in a thickened bowel segment. This is important for patient management because fibrotic stenosis often requires operative intervention, whereas active inflammation can respond to medical management.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Radiological imaging is an important non-invasive method for the diagnosis of UC. Compared with CT, MRI has several advantages, such as high-resolution imaging, detailed soft tissue background, and no need for ionizing radiation [19][20][21]. With a higher spatial resolution and multi-parameter imaging, MRI is suitable for the early diagnosis of UC and assessment of disease activity [22].…”
Section: Discussionmentioning
confidence: 99%
“…So far, magnetic resonance (MR) enterography has gained a central role in imaging pediatric IBD of disease activity [96]. In some reports the findings in MR enterography (MRE) images have probably overestimated inflammation, when compared to findings detected while at surgery [101]. However, the published data on MR investigations for pediatric IBD patients has mostly been restricted to patients with Crohn´s disease [96][97][98][99][100].…”
Section: Improvements In Imagingmentioning
confidence: 99%